2022
DOI: 10.1111/hepr.13797
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of atezolizumab plus bevacizumab treatment for unresectable hepatocellular carcinoma in patients with Child‐Pugh class A or B liver function in real‐world clinical practice

Abstract: Background/Aim Atezolizumab plus bevacizumab (Atez/Bev) treatment is recommended for unresechepatocellular carcinoma (u‐HCC) patients classified as Child‐Pugh A (CP‐A). This study aimed to elucidate the prognosis of patients treated with Atez/Bev, especially CP‐A and ‐B cases. Materials/methods From September 2020 to March 2022, 457 u‐HCC patients treated with Atez/Bev were enrolled (median age 74 years, male:female = 368:89, CP‐A:CP‐B = 427:30, Child‐Pugh score [CPS] 5:6:7:8:9 = 271:156:21:8:1). Therapeutic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
69
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 54 publications
2
69
2
Order By: Relevance
“…The nature and severity of treatment-related AEs observed in this study differed substantially from those previously reported [ 8 , 21 , 22 , 23 , 27 , 28 , 29 , 30 , 31 ]. In contrast, we detected significant deterioration in liver functional reserve including albumin levels, Child–Pugh score, ALBI score, and the appearance of ascites within the initial 3 months of treatment.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…The nature and severity of treatment-related AEs observed in this study differed substantially from those previously reported [ 8 , 21 , 22 , 23 , 27 , 28 , 29 , 30 , 31 ]. In contrast, we detected significant deterioration in liver functional reserve including albumin levels, Child–Pugh score, ALBI score, and the appearance of ascites within the initial 3 months of treatment.…”
Section: Discussioncontrasting
confidence: 85%
“…In contrast, we detected significant deterioration in liver functional reserve including albumin levels, Child–Pugh score, ALBI score, and the appearance of ascites within the initial 3 months of treatment. Although the findings of some studies have indicated that ALBI scores tend to decline within the first few weeks of treatment, observations in most previous studies have tended to indicate that these scores do not deteriorate in response to Atez/Bev [ 23 , 27 , 29 , 30 , 31 ]. The fact that we detected a positive correlation between the ∆ ALBI score and ∆ PIVKA-II in the present study (coefficient of correlation = 0.286, p = 0.034; Figure S4 ) would tend to imply that a deterioration in the ALBI score is associated with the progression of HCC itself, rather than with the AEs of this treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, most patients had a Child-Pugh score of 7. A recent study reports that the median PFS for atezolizumab and bevacizumab is similar in patients with a Child-Pugh score of 6 (5.1 months, 95%CI: 3.8–6.4 months) and 7 (6.3 months, 95% CI: 2.3–7.0 months) [ 24 ]. This might explain the better PFS of patients with Child-Pugh B in this study; however, further studies with larger sample sizes are required to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…The median OS (95% CI) was 7.6 (4.4–10.5) months. A retrospective study to examine the outcomes and safety of patients treated atezolizumab plus bevacizumab between CP-A (n=427) and CP-B (n=30) status has just been published ( 6 ). In terms of AEs, patients with CP-B significantly more frequently experienced appetite loss and edema/ascites than those with CP-A.…”
mentioning
confidence: 99%